Prevalence of human papillomavirus infection among 71,435 women in Jiangxi Province, China - Tian-Yu Zhong; Ji-Chun Zhou; Rong Hu; Xiao-Na Fan; Xiao-Ying Xie; Zhao-Xia Liu; Min Lin; Yi-Guo Chen; Xiao-Mei Hu; Wei-Hua Wang; Long Li; Hua-Ping Xiao (Elsevier, 2017)
Cervical cancer is the third most common cancer in women worldwide. Human papillomavirus (HPV) has been identified as an etiological factor for cervical cancer. Data on the prevalence and subtype distribution of HPV infection in Jiangxi Province are incomplete. In this study, we investigated HPV subtype distribution and prevalence in Jiangxi Province between August 1, 2010, and December 31, 2015. A total of 71,435 individuals ranging in age from 16 to 77 years were recruited. Cervicovaginal swabs were collected from each participant, and HPV screening was performed. Our results showed that the HPV prevalence was 22.49% in Jiangxi Province. Overall, 14.99% of individuals were positive for a single HPV type, and 7.49% were positive for multiple types. The most frequently detected low-risk genotypes were HPV-6, and high-risk genotypes were HPV-16, -18, -33, -52, and -58. The prevalence and type distribution of HPV infection exhibits regional and age differences; Yingtan had the highest incidence for high-risk HPV infection (32.00%), and peaks in the frequencies of HPV infections were seen for patients under 20 and over 60 years of age. In conclusion, we present data showing that the HPV prevalence varies significantly with age and regions in Jiangxi Province. These results can serve as valuable reference to guide Jiangxi cervical cancer screening and HPV vaccination programs. Keywords: Human papillomavirus, Jiangxi Province, Subtypes, Age